Determinan Return On Asset Dengan Non Performing Financing Sebagai Variabel Moderasi - Anwar, Febrianto A.; Arianta, Yusvita Nena (Mandiri : Jurnal Akuntansi dan Keuangan, 2022)
The purpose of this study was conducted to determine the effect of CAR, FDR, TPF, and ZPR, on profitability with NPF as a moderating variable. This study uses quantitative research using multiple regression analysis as data analysis. This study uses panel data in the form of Random Effect annual data of CAR, FDR, TPF, ZPR, NPF, ROA at Islamic commercial banks registered with OJK for the 2016-2019 period. The data obtained in this study were analyzed using the eviews 9 application tool. The results of this study indicate that the CAR variable has no significant negative effect on Profitability (ROA). FDR has no significant negative effect on profitability (ROA). TPF has no significant negative effect on profitability (ROA). ZPR has no significant positive effect on profitability (ROA). NPF-moderated CAR has no significant positive effect on profitability (ROA). FDR moderated by NPF has an insignificant negative effect on profitability (ROA). TPF moderated by NPF has no significant positive effect on profitability (ROA). ZPR moderated by NPF has an insignificant negative effect on profitability (ROA).